Aktivitas nokturnal vektor demam berdarah dengue di beberapa daerah di Indonesia - Upik Kesumawati Hadi; Susi Soviana; Dwi Djayanti Gunandini (Jurnal Entomologi Indonesia, 2012)
The continous presence of dengue virus infection presents a serious health problem in many tropical areas of the world because of the severe and often fatal disease in children. Dengue viruses are transmitted to human through the biting of infected mosquitoes, especially Aedes aegypti and Aedes albopictus. This paper reported the nocturnal of biting activity of Ae. aegypti and Ae. albopictus in several areas of Indonesia. Natural population of Aedes was collected by bare leg collection and resting collection from 18:00 to 06:00 out door and indoor. The biting activities of Ae. aegypti and Ae. albopictus occurred throughout the night from 18:00 to 05:50 out door and indoor in Cikarawang, Babakan, and Cibanteng Kabupaten Bogor (2004); Cangkurawuk Darmaga Bogor (2005, 2007); Pramuka island, Pari island, Kepulauan Seribu (2008); Gunung Bugis, Gunung Karang, Gunung Utara Balikpapan (2009); and Kayangan, Lombok Utara (2009). These results showed that the biting activities of Ae. aegypti dan Ae. albopictus did not only occur diurnally but also nocturnally.